The effect of syrup simplex concentration on the physicochemical stability of Gembili’s inulin (Dioscorea esculenta (Lour.) Burkill) nanosilver colloid - Ermawati, Dian Eka; Hanuriansyah, Yavi (Pharmaciana, 2024)
Gembili tuber's inulin is a successful bioreductor agent that forms a nanosilver with a size of 481.4 nm and is stable for 30 days at 4 °C storage. That nanosilver has immunomodulatory activity and is proven safe from the results of acute toxicity tests at a dose of 4 mg/kgBB. However, a drug delivery system is needed to be developed as a supplement product. The syrup was chosen because it is free of alcohol, has a better taste, measured dose, and stability of the active substance compared to elixir, solution, and suspension. Simplex syrup as a syrup base affects stability because it has the potential to form crystals during storage. This research aims to determine the effect of simplex syrup concentration on the stability of nanosilver syrup. The research was conducted with the biosynthesis process using gembili's inulin, nanosilver characteristic, modified syrup formula, and stability test. Nanosilver syrup was prepared by modifying the simplex syrup concentration of 20%, 40%, and 60%. Nanosilver was added at 4 mg/KB b.w, then tested the physicochemical; stability, including organoleptic, pH, and viscosity, before and after storage with temperature variations of 4 °C and 40 °C for six cycles. The best formula then analysis of sugar reduction content and FT-IR. Data analysis using SPSS 21.0 Windows with One-way ANOVA test, Post Hoc, and Paired T-Test. The results showed that the concentration of simplex syrup affected consistency, pH, and viscosity. The simplex syrup concentration of 60% met the requirement with a medium thick consistency, pH 5.25±0.03, a viscosity of 92±2.6 cps, reducing sugar content was 20.59% ±0.002, and the FTIR profile showed that it still contained nanosilver which was indicated by the presence of Ag-N groups compared to silver nitrate solution.